The Exhortation to Candidates for Ascetical Vows at Baptism in the Ancient Syriac Church - Murray, Robert 1925- (1974)
Throughout the present century historians of Christian asceticism, especially in the Syriac-speaking area, have returned repeatedly to the problem posed by a passage in Aphrahat's seventh Demonstration, the natural implication of which seems to be that in his day baptism was reserved for those who consecrated themselves to Christ in virginity or by renouncing marital intercourse, to become members of the ‘Covenant’ (qyāmâ) which was evidently regarded as the core or heart of the Church. The question was raised provocatively by F. C. Burkitt (1899, 1904) and taken up by R. H. Connolly, with an intervening reply by Burkitt, in 1905-7. Connolly rightly argued that by Aphrahat's time (fl. 336-45) married people must have been regarded as members of the Church, and that the ‘penitents’ discussed by Aphrahat were Christians who had ‘fallen’ after baptism, but he overplayed his hand in identifying the Bnay Qyāmâ simply as ‘monks’. An undertone of denominational controversy remained throughout the subsequent discussion, continued by (among others) H. Koch (1911), K. Müller (1927) and E.J. Duncan (1945). It was A. Vööbus who showed the way out of the impasse by his perceptive suggestion that the exhortation in Dem. VII is a liturgical text which had survived into Aphrahat's day but whose restrictive implications were no longer in force. At the same time, under the powerful impetus of the discoveries of the Qumran, Nag Hammadi and Manichaean documents, with consequently increasing understanding of early Jewish Christianity in its many varieties, and realization that Syrian asceticism was not derivative from Egypt but probably earlier, the basic concepts and terminology of asceticism were being studied anew by A. Adam, E. Beck, G. Kretschmar, P. Nagel, M. Black, J. Gribomont, A. Guillaumont and others. Study of early Syriac asceticism continues, as is shown by G. Nedungatt's recent articles but there still remains more to be done to follow up Vööbus's hint about the genre of the exhortation quoted by Aphrahat in Dem. VII.